AKAD MUDHARABAH DALAM PERBANKAN SYARIAH - Sri Astutik (Faculty of Law, University of Dr. Soetomo, 2017)
Sharia Bank has the function of collecting funds from the community and channeling funds to the public. One of the contracts used in the transaction is done by Mudharabah contract. Mudharabah is a business cooperation between two parties where the first party (shahibul maal) provides all capital, while the other party becomes the manager (mudharib). Making Mudharabah Agreement as part of Muamalah can be modified in accordance with the times and adjust to the needs, however, making mudharabah contract in sharia banking must still fulfill the principles of sharia.